FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SOCIAL MEDIA FATIGUE SELAMA PEMBELAJARAN DARING PADA MAHASISWA KEPERAWATAN - Suwari, Komang; Utami, Putu Ayu Sani; Raya, Nyoman Agus Jagat (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p14, 2023)
Social media fatigue is prone to be experienced by students during online learning which results in adverse effects on physical and mental health such as depression, anxiety, unstable emotions, and academic decline due to the use of social media. This study aims to determine the factors associated with social media fatigue during online learning for nursing students at Udayana University. The research design used a quantitative approach with a cross sectional study method. The research sample used probability sampling with stratified random sampling technique (n=180). Data were collected using the Educational Stress Scale for Adolescents (ESSA), Pittsburgh Sleep Quality Index (PSQI), Connor-Davidson Resilience Scale (CD-RISC) and Social Media Fatigue Scale (SMFS) questionnaires. The results showed 156 (86,7%) respondents had a moderate level of social media fatigue. The correlation test on social media fatigue shows that the respondent's characteristics have no relationship (p value of age = 0,999; gender = 1,000; GPA = 1,000). Likewise with sleep quality (p value = 0,162) and resilience (p value = 0,333). However, academic stress has a significant relationship with social media fatigue (p value = 0,001). Social media fatigue can be influenced by academic stress which causes students to tend to use social media during the learning process. Prevention of social media fatigue can be done by exercising self-control such as self-healing and using social media effectively, especially as a learning tool.